Analysis of C-Reactive Protein, Neutrophil-to-Lymphocyte Ratio, PaO2/FiO2 Ratio on the Success of High Flow Nasal Cannula Usage in Hospitalized COVID-19 Patients - Arina Aftritia Izzati; Ungky Agus Setyawan; Rezki Tantular (Indonesian Society of Respirology (ISR), 2023)
Background: Several studies had shown High Flow Nasal Cannula (HFNC) is effective in treating hypoxemic COVID-19 patients. The C-Reactive Protein and Neutrophil-to-Lymphocyte Ratio is an inflammatory marker that could predict the severity of COVID-19, where the P/F ratio infers oxygenation status. Since COVID-19-related ARDS is closely related to a hyper-inflammatory state and HFNC becomes widely utilized for hypoxemic patients, it has become important to discover reliable inflammatory biomarkers related to therapeutic HFNC success. This study aims to assess the factors that influence the success of HNFC therapy, in terms of demographic and laboratory profiles of CRP, NLR, and P/F ratio. Method: A retrospective, single-center cohort study was conducted in a tertiary care hospital in Malang, East Java from January to March 2022. Subjects of 31 PCR-confirmed, hospitalized COVID-19 patients who were treated with HFNC were included. Results: This study involved 2 groups comprised of 19 subjects with successful HFNC and 12 patients who failed. Significant demographic factors affecting successful HFNC were female gender (OR=1.46 95% CI=1.08-1.99; P=0.037) and occupation type (P=0.023). Whereas, biomarkers of CRP (8.90±6.8 mg/L vs 12.39±11.7 mg/L; P=0.656), NLR (7.24±4.66 vs 12.85±12.9; P=0.243) and P/F ratio (171.40±54 vs 148.00±40; P=0.219) were found to be non-significant between successful and failed HFNC cohorts, respectively. Conclusion: HFNC could provide a specific positive end-expiratory pressure in COVID-19 patients with contributing factors of successful HFNC being female and occupational type. However, CRP, NLR, and P/F did not contribute significantly to HFNC's success.